Development and mechanistic studies of calcium–BINOL phosphate-catalyzed hydrocyanation of hydrazones - Tortora, Carola; Fischer, Christian Andreas; Kohlbauer, Sascha; Zamfir, Alexandru; Ballmann, Gerd M.; Pahl, Jürgen; Harder, Sjoerd; Tsogoeva, Svetlana B. (Beilstein Journal of Organic Chemistry, 2025)
Asymmetric hydrocyanation of hydrazones, catalyzed by a calcium–BINOL phosphate complex, has been studied for the first time both experimentally and computationally with DFT methods. A full catalytic cycle for the enantioselective synthesis of α-hydrazinonitriles is proposed based on insights gained from DFT calculations. Trimethylsilyl cyanide (TMSCN) has been used as a sacrificial cyanide source. We found that isocyanide (rather than cyanide) is a preferred coordination to calcium during the catalytic cycle, while the active catalyst prefers a side-on coordination of cyanide. The configuration-determining step is a hydrocyanation via a calcium isocyanide complex, whereas the rate-limiting step is that which recovers the calcium catalyst and replaces the TMS-bound product from the catalyst. While our experimental data demonstrate enantioselectivity values as high as 89% under certain conditions, the overall enantioselectivity achieved with the calcium catalyst remains modest, mainly due to competing pathways for the Z- and E-hydrazone isomers leading to opposite enantiomers. The experimental results confirm these computational proposals.
Keywords: asymmetric synthesis; calcium–BINOL phosphate catalysis; hydrocyanation; hydrazones; isocyanides